Comparative Analysis Of The Methodology Of Organizing Physical Education Lessons In Grades I–Xi And Improving Teaching Methods (Journal of Pedagogical Inventions and Practices, 2025)
This article considers the issue of increasing the physical health and movement activity of the younger generation in recent years in our Republic as one of the global problems. It will be mentioned about the reforms carried out in this direction, the scientific research work carried out by scientists on the issues of further improving the quality of physical education lessons and their comparative analysis.